Training and supervision in specialized cognitive behavior therapy : methods, settings, and populations - Storch, Eric A.; Abramowitz, Jonathan S.; McKay, Dean, 1966- (American Psychological Association, 2022)
"This book describes training, supervision, and consultation with specialized cognitive behavior therapy approaches to ensure proper implementation across diverse settings and populations"--